A study of the N=28 neutron shell via g-factor measurements in neutron-rich Cl isotopes - De Rydt, M.; Neyens, G.; Mertzimekis, T. J.; E513 Collaboration at GANIL, for the (HNPS Advances in Nuclear Physics, 2020)
A series of g-factor measurements in the Cl isotopes created as secondary radioactive beams at intermediate energies and employing the β-NMR technique have been recently carried out at GANIL. The results attempt to shed light on several open questions for the ground state properties of Cl isotopes, located just off the very interesting region of the island of inversion. Preliminary experimental results are presented and compared to shell-model calculations around N=28.